2012
DOI: 10.1186/1757-7241-20-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance of two different chest tubes with either a sharp or a blunt tip for thoracostomy in 100 human cadavers

Abstract: BackgroundEmergent placement of a chest tube is a potentially life-saving procedure, but rate of misplacement and organ injury is up to 30%. In principle, chest tube insertion can be performed by using Trocar or Non-trocar techniques. If using trocar technique, two different chest tubes (equipped with sharp or blunt tip) are currently commercially available. This study was performed to detect any difference with respect to time until tube insertion, to success and to misplacement rate.MethodsTwenty emergency p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…To our knowledge the only detrimental effect of BMI previously shown has been a study assessing time to completion which was detrimental with increased BMI 13 . In our analysis, an increased BMI ≥ 30 is associated with an increased angle of insertion, as to which causes or contributes to complications remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge the only detrimental effect of BMI previously shown has been a study assessing time to completion which was detrimental with increased BMI 13 . In our analysis, an increased BMI ≥ 30 is associated with an increased angle of insertion, as to which causes or contributes to complications remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In our study 31% of units had only chest tubes with trocars, while 38% of units had both trocar and non-trocar chest tubes. Ortener et al have shown that chest drain insertion with trocars to be associated with a 6-14 % operator related complication rate [3]. No difference in the average performance time could be found between the two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-availability of equipment has been highlighted as a cause of iatrogenic complications in UK [2]. Furthermore, the use of chest drains with sharp trocar tips have been found to cause a 6-14% increase of operator-related complications [3]. British Thoracic Society (BTS) guidelines have listed out the required equipment for the safe insertion of a chest drain and also recommended the use of blunt dissection and the use of chest drains without trocars [4].…”
Section: Introductionmentioning
confidence: 99%
“…These are meant to insert in intercostal space after making a small skin incision, without dissecting the intercostal muscles. Although, this makes the procedure fast, there is a higher risk of injury to the intrathoracic organs and as such use of chest tubes with trocars should be discouraged [3,5,6]. Most of the chest tubes are open from one end while the other end is sealed.…”
Section: Commercially Available Chest Tubesmentioning
confidence: 99%